Effects of different insecticides on egg, larva and adult of tomato leaf miner, Tuta absoluta (Lepidoptera: Gelechiidae) - Ahmad Moeini-Naghade; Aziz Sheikhigarjan; Naser Moeini-Naghadeh; Abbas Ali Zamani (Journal of Crop Protection, 2020)
Tomato leaf miner, Tuta absoluta (Meyrick), is a serious pest of the greenhouse in Iran. Chemical control is the main method in high infestation conditions to deal with this pest. In this study, the efficacy of five insecticides from different groups consisting of abamectin, spinosad, imidacloprid, indoxacarb and cypermethrin was examined on the egg, larvae and adult stages of T. absoluta in laboratory conditions. The LC50 values of the insecticides were estimated at the larval stage. The results showed that abamectin had the most and imidacloprid had the least ovicidal effect. None of the tested insecticides had a satisfactory effect on the adult stage. The maximum adulticide impact was 40% for spinosad. Abamectin with 0.45 mg ai.l-1 of LC50 value had the most toxicity and imidacloprid with 980 mg ai.l-1 of LC50 value had the least toxicity on the third instar larvae. According to the findings, abamectin and spinosad had the highest toxicity against three developmental stages (egg, larvae and adults) of the pest and can be used in infested tomato fields, when all life stages of T. absoluta are present at the same time. Meanwhile, it is recommended to use selective insecticides such as indoxacarb, when natural enemies are very active or the population of the tomato leaf miner is mostly at the larval stage.